Zika Virus–Associated Guillain-Barré Syndrome in a Returning US Traveler. Issue 6 (November 2018) - Beattie, Jason; Parajuli, Sunita; Sanger, Matthew; Lee, Gregory; Pleninger, Perrin; Crowley, George; Kwon, Sophia; Murthy, Vivek; Manko, Jeffrey A.; Caplan, Arthur; Dufort, Elizabeth; Pastula, Daniel M.; et al.
Abstract : Abstract: Zika virus (ZIKV) infection has been associated with Guillain-Barré syndrome (GBS). Roughly 60% of people in countries such as the United States live in areas at risk of seasonal spread of ZIKV. Zika virus belongs to a class of diseases that is not typically seen in hospital settings across the United States and Europe. We describe the case presentation, management, and treatment of ZIKV infection complicated by GBS. A 64-year-old woman with recent travel to the Dominican Republic presented with rash followed by an acute, ascending polyneuropathy consistent with GBS. She was confirmed to have an acute ZIKV infection by detection of ZIKV nucleic acid by reverse transcription–polymerase chain reaction. She met Brighton Collaboration criteria level 1 evidence for GBS. She received 2 courses of intravenous immunoglobulin and slowly improved, but still had weakness at discharge. More research is needed to identify the pathophysiology behind ZIKV-associated GBS and its optimal treatment. Prevention is fundamental to limiting infection and spread of ZIKV. Abstract : A returning US traveler contracted Zika virus and associated Guillain-Barr é syndrome. She received supportive care including endotracheal intubation and tracheostomy. After receiving two courses of intravenous immunoglobulin, she slowly improved but still had weakness at discharge. This case report should serve as a reminder of the danger of Zika virus and presents a method of treatment for this serious complication of Zika infection.